Agronomic association of Vrn, Ppd, Rht genes and identified QTLs under contrasting tillage conditions in wheat - Yadav, Rajbir; Sagar, Vidya; Jain, Neelu; Gaikwad, KB (Journal of Cereal Research, 2014)
Improved varieties have played important role in higher yieldrealization in tandem with improved management practices.Conservation agriculture as an improved environment for higherproduction requires adaptive variety to further the yield gain. Highereffect of environment along with equally important GÃ—E makesselection on the basis of phenotypic traits more risky and less rewarding.Molecular markers with lesser effect of environment and independentof stage and condition for their expression present attractive optionto breeders to improve selection efficiency. Various Vrn, Ppd and Rhtgenes along with number of QTLs identified by researchers haveadaptive role in wheat. Genotypes showing differential adaptivenesswere grown under three contrasting environments generated bydifferent tillage-sowing methods. Gene specific markers were scoredand genotypes were grouped as per markers profile. Grouping on thebasis of markers was correlated with phenotypic grouping, thoughnot so strongly, under different environments, picking conservationagriculture adaptive genotypes under one node and genotypes adaptedfor conventional tillage in another node. Contrasting pool created byidentified QTLs under its adaptive growing environment does not showany differentiating ability and therefore requires further validationbefore use in breeding programme.